Reduction in Red Blood Cell Transfusions Among Preterm Infants: Results of a Randomized Trial With an In-Line Blood Gas and Chemistry Monitor - Widness, John A. (2005)
BACKGROUND: Critically ill, extremely premature infants develop anemia because of intensive laboratory blood testing and undergo multiple red blood cell (RBC) transfusions in the early weeks of life. To date, researchers have had only limited success in finding ways to reduce transfusions significantly in this patient population. OBJECTIVE: To reduce RBC transfusions for these infants by using a point-of-care bedside monitor that returns analyzed blood to the patient. DESIGN, SETTING, AND PATIENTS: This was a prospective, 2-center, randomized, open, controlled, clinical trial with a 1:1 assignment of extremely low birth weight infants (weighing 500–1000 g at birth) to control or monitor groups and analysis with the intention-to-treat approach. Predefined RBC transfusion criteria were applied uniformly in the 2 groups. INTERVENTIONS: Clinical treatment of study subjects with an in-line, ex vivo, bedside monitor that withdraws blood through an umbilical artery catheter, analyzes blood gases and sodium, potassium, and hematocrit levels, and returns the sample to the patient. MAIN OUTCOME MEASURES: The total volume and number of RBC transfusions during the first 2 weeks of life and the total volume of blood removed for laboratory testing. RESULTS: The trial was terminated prematurely when one center's NICU changed its standard method of laboratory testing. In the first 2 weeks of life, there was a nonsignificant 17% lower cumulative RBC transfusion volume in the monitor group (n = 46), compared with the control group (n = 47). However, data from the first week only (the period of greater catheter use) demonstrated a significant 33% lower cumulative RBC transfusion volume in the monitor group. Cumulative phlebotomy loss was ~25% less in the monitor group throughout the 2-week study period. There was no difference between groups in neonatal mortality, morbidity, and neurodevelopmental outcome rates at 18 to 24 months. This is the first randomized trial documenting that RBC transfusions administered to neonates can by reduced by decreasing laboratory phlebotomy loss. CONCLUSIONS: As long as an umbilical artery catheter is available for blood sampling with an in-line blood gas and chemistry monitor, significant reductions in neonatal RBC transfusions can be achieved. The patients most likely to benefit from monitor use are the smallest, most critically ill newborns.